'Why is survival with triple negative breast cancer so low? insights and talking points from preclinical and clinical research'. (2nd December 2022) - Passalacqua, Maria Ilenia; Rizzo, Graziella; Santarpia, Mariacarmela; Curigliano, Giuseppe
ABSTRACT: Introduction: Triple negative breast cancer is typically related to poor prognosis, early metastasis, and high recurrence rate. Intrinsic and extrinsic biological features of TNBC and resistance mechanisms to conventional therapies can support its aggressive behavior, characterizing TNBC how extremely heterogeneous. Novel combination strategies are under investigation, including immunotherapeutic agents, anti-drug conjugates, PARP inhibitors, and various targeting agents, exploring, in the meanwhile, possible predictive biomarkers to correctly select patients for the optimal treatment for their specific subtype. Areas covered: This article examines the main malignity characteristics across different subtype, both histological and molecular, and the resistance mechanisms, both primary and acquired, to different drugs explored in the landscape of TNBC treatment, that lead TNBC to still has high mortality rate. Expert opinion: The complexity of TNBC is not only the main reason of its aggressivity, but its heterogeneity should be exploited in terms of therapeutics opportunities, combining agents with different mechanism of action, after a correct selection by biologic or molecular biomarkers. The main goal is to understand what TNBC really is and to act selectively on its characteristics, with a personalized anticancer treatment.